Sofrimentos de Amor - Reina Marisol Troca Pereira (Autores Gregos e Latinos - Textos, 2015)
The Love Stories of Parthenius is the only wholly extant work of this author. This selection of Hellenistic prose includes 36 short mythological stories dedicated to the poet Cornelius Gallus. This valuable example illustrates the influence of Greek Mythography in late Republican and Augustan Rome. The mythological and pseudo-historical stories on the subject of love suffering (Erotica Pathemata) are presented as summarized sentimental episodes extracted from several Greek authors, generally acknowledged by Parthenius. Other themes such as hospitality, betrayal, secrecy, suicide, romantic love and sexual passion, incest, pedophilia, same-sex desire or necrophilia are also discussed.